Genome Editing - Turksen, Kursad (Springer International Publishing : Imprint: Springer, 2016)
This timely volume explores the use of CRISPR-Cas9 for genome editing, presenting cutting-edge techniques and their applications in treatment of disease. The chapters describe latest methods such as use of targetable nucleases, investigation of the non-coding genome, mouse genome editing, increasing of knock-in efficiency in mouse zygotes, and generation of reporter stem cells; the text contextualizes these methods in treatment of cardiovascular disease, diabetes mellitus, retinitis pigmentosa, and others. The final chapters round out the book with a discussion of controversies and future directions. Genome Editing is an essential, of-the-moment contribution to this rapidly growing field. Drawing from a wealth of international perspectives, it presents novel techniques and applications for the engineering of the human genome. This book is essential reading for all clinicians and researchers in stem cells, regenerative medicine, genomics, biochemical and biomedical engineering- especially those interested in learning more about genome editing and applying it in a targeted, specific way.